Extrathyroidal Calcitonin Secreting Tumors: Pancreatic Neuroendocrine Tumors in Patients With Multinodular Goiter. Issue 3 (January 2016) - Giannetta, Elisa; Gianfrilli, Daniele; Pozza, Carlotta; Lauretta, Rosa; Graziadio, Chiara; Sbardella, Emilia; Baroli, Alberto; Caronna, Roberto; Chirletti, Piero; Lenzi, Andrea; Isidori, Andrea M.
Abstract : Abstract: Calcitonin is the hallmark of medullary thyroid carcinoma. However, extrathyroidal neuroendocrine tumors can also release calcitonin. We report 2 cases of calcitonin-secreting pancreatic tumors found in asymptomatic patients with thyroid nodules referred to our center within 11 months. Case 1: A man initially referred for thyroid nodule characterization was found to have hypercalcitoninemia (>200 pg/mL) during non-neoplastic fine-needle aspiration. Case 2: A woman evaluated for liver metastasis was found to have hypercalcitoninemia and multinodular goiter. Our research emphasizes that marked hypercalcitoninemia in the presence of thyroid nodules is not necessarily due to medullary thyroid carcinoma; awareness of this could avoid unnecessary thyroidectomy. The lack of specific symptoms related to hypercalcitoninemia may be the reason that the prevalence of calcitonin-secreting pancreatic tumors is underestimated.